PENGARUH PERMAINAN TRADISIONAL " ENGKLEK " TERHADAP PERKEMBANGAN MOTORIK ANAK DI TKIT BAITURRAHMAN PRAMBANAN KABUPATEN KLATEN TAHUN AJARAN 2015/2016 - ROCHMANI, IMMA'U; , Dra. Surtikanti, SH. M.Pd (2016)
The purpose of this study was to determine the effect of traditional game "engklek" towards motoric development for children TKIT Baiturrahman Prambanan Klaten academic year 2015/2016. This research method is an experiment with the type of one group pretest-posttest, accompanied by hypothesis testing. Subjects in this study were children in group A TKIT Baiturrahman Prambanan Klaten academic year 2015/2016, amounting to 32 children. Data collection techniques gained through observation guidelines. Data were analyzed using descriptive and inferential analysis. Descriptive analysis is used to determine the status gross motor development of children before and after the experiment. Inferential analysis to test the hypothesis using T test in SPSS 16 for windows by Paired sample t-test. Based on the analysis of the results of research using t-test values obtained t_hitung = -5.292 and -1.696 with probability t_tabel = 0,000 <α = 0.05, then Ho rejected and Ha accepted, which means there is an influence of traditional games towards motoric development of children in TKIT Baiturrahman Prambanan Klaten Year 2015/2016.